Inggris - Dicky Maskurido; Sukendro Sukendro; Sugih Suhartini (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
This study was conducted to address the problem of low leg muscle power among beginner volleyball players, which negatively affects the effectiveness of smash and block techniques. The purpose of this study was to examine the effect of mud jumping exercise variations on leg muscle power in beginner players of the Rottan Volleyball Club, Kuala Betara District. This study employed a quasi-experimental method using a one-group pre-test–post-test design. The research participants consisted of all beginner players at the Rottan Volleyball Club, totaling 13 athletes, selected using a total sampling technique. The training intervention involved structured mud jumping exercise variations as a modified plyometric program. Leg muscle power was measured using a vertical jump test, and the data were analyzed using descriptive statistics and a paired-sample t-test at a significance level of 0.05. The results showed a significant increase in leg muscle power following the mud jumping training program. The average post-test vertical jump scores were higher than the pre-test scores, and the results of the paired-sample t-test indicated a statistically significant difference between pre-test and post-test measurements. It can be concluded that mud jumping exercise variations have a significant effect on improving leg muscle power in beginner volleyball players. Therefore, mud jumping exercises can be recommended as an effective and practical training method to enhance lower limb explosive power in beginner volleyball athletes